IMPELENTASI METODE PROTOTYPING PADA PERANCANGAN TAMPILAN UI/UX APLIKASI ANDROID BACA LIGHT NOVEL - Rahmad Rama Dani; Karnadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of digital technology has allowed for wider access to various forms of content, including Light Novels, which are increasingly popular among global readers. However, there are still limitations in the existing Light Novel reading application, especially in terms of user interface (UI) and user experience (UX). This research aims to design the UI/UX of an Android-based Light Novel reading application by applying a prototyping method. This method allows for iterative design creation and evaluation to ensure a functional, aesthetic, and user-friendly interface. The results of this study include the design of several key features, such as an update page, a list of popular Light Novels, a genre-based search feature, as well as a community page and user profiles. With a user-centric design approach, this research is expected to provide a more comfortable and interesting reading experience for Light Novel fans, as well as support the development of digital literacy in the modern era.